Trust and Uncertainty: How to Communicate Successfully - Olga Griaznova (Journal of Economic Sociology, 2015)
This review is devoted to a description and analysis of the book by Diego Gambetta, Codes of the Underworld: How Criminals Communicate. The author studied elements of communicative action basing on signaling theory. In part, he continues the tradition of symbolic interactionism elaborated by Goffman. But, at the same time, he extends the concept “symbol” and narrows down contextual frames to situations of uncertainty and limited trust between agents. Gambetta also refers to economic theory and game theory to analyze and interpret actions of agents in this context. This review aims at a theoretical systematization and generalization of key findings.This review discusses several important issues that are essential to understand the main arguments and opinions of the book. First, Griaznova places the book into the context of Gambetta’s previous publications. In this respect it is regarded as a significant step in the development of his core ideas of the mutual dependence of the volume of social “investment” in communication with the level of uncertainty and risk. Next, the review analyses in detail the content of the work. In particular, signaling theory, signal types and their empirical indicators are examined in turn. In the conclusion, the review considers the contribution of this research to the understanding of communication practices. Analysis of communication between criminals has a number of obvious advantages, but researchers face limits in studying this topic. On the one hand, a researcher would have an opportunity to put a communicative act into the context of higher uncertainty and trace the relationship between the level of risk and the amount of “investment”. However, on the other hand, a researcher is limited in choice of data collection method.